EL SISTEMA METODOLOGICO Y SU INCIDENCIA EN EL DESARROLLO DE LA ESTRUCTURA INTEGRAL CONSCIENTE EN EL AREA DE MATEEMATICA DE LAS ESTUDIANTES DEL SEGUNDO AÑO DE BACHILLERATO EN LA ESPECIALIZACION FISICO-MATEMATICAS DEL INSTITUTO TECNOLOGICO "RIOBAMBA". - VICTOR MANUAL BORJA MOROCHO (2004)
THE METHODOLOGICAL SYSTEM AND ITS IMPACT ON THE DEVELOPMENT OF THE CONSCIOUS INTEGRAL STRUCTURE IN THE AREA OF MATHEMATICS OF THE SECOND YEAR OF HIGH SCHOOL STUDENTS IN THE PHYSICAL-MATHEMATICAL SPECIALIZATION OF THE "RIOBAMBA" INSTITUTE OF TECHNOLOGY.